Pemberian bantuan berupa scaffolding untuk meningkatkan kemampuan berpikir kreatif siswa kelas V SDN 01 Pedawang - Ika Martiana (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The purpose of this study is to improve the creative thinking skills of fifth grade students of SDN 01 Pedawang through scaffolding assisted learning. This research was designed in two cycles, each cycle with the stages of planning, implementing actions, observing and reflecting. The results showed that the students were at a moderately creative level as many as 7 students, and 2 other students were at a less creative level; scaffolding-based mathematics learning can improve student learning outcomes. This can be seen in the percentage of students' classical completeness which initially in the first cycle reached 66.67% to 88.89% in the second cycle. Furthermore, scaffolding-based mathematics learning can increase student activity.